2012
DOI: 10.4037/ccn2012123
|View full text |Cite
|
Sign up to set email alerts
|

Managing Risk of Complications at Femoral Vascular Access Sites in Percutaneous Coronary Intervention

Abstract: Percutaneous coronary intervention for acute coronary syndrome or non–ST-elevation myocardial infarction requires the use of potent oral and intravenous anti-platelet and antithrombin medications. Although these potent antithrombotic agents and regimens may increase the effectiveness of percutaneous coronary intervention, they are also generally associated with an increased risk of vascular access complications such as hematoma, retroperitoneal hematoma, pseudoaneurysm, arterial occlusion, and arteriovenous fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 74 publications
5
51
0
2
Order By: Relevance
“…In our study, multiple hospitals of differing sizes were taken into account which provides a more realistic picture of daily routine care. Similar to other studies we found factors that significantly influence the occurrence of complications like e.g., the protective effect of male gender and an increasing risk with the comorbidity renal failure [15,16], indicating the external validity of our analysis. Another strength is that we did separate analyses on diagnostic and interventional procedures.…”
Section: Interventional Cardiology Journal Issn 2471-8157supporting
confidence: 71%
See 1 more Smart Citation
“…In our study, multiple hospitals of differing sizes were taken into account which provides a more realistic picture of daily routine care. Similar to other studies we found factors that significantly influence the occurrence of complications like e.g., the protective effect of male gender and an increasing risk with the comorbidity renal failure [15,16], indicating the external validity of our analysis. Another strength is that we did separate analyses on diagnostic and interventional procedures.…”
Section: Interventional Cardiology Journal Issn 2471-8157supporting
confidence: 71%
“…We identified the following risk factors for complications by literature search: increasing age, female gender, obesity [15], hypertension [16], Peripheral Vascular Disease (PVD), Coronary Artery Disease (CAD) [17], diabetes mellitus [18], renal dysfunction [16] and the intake of antiplatelet and anticoagulant medication [17,19]. In the dataset, we identified these confounding variables through ICD and OPS codes from inpatient and outpatient records of the insurance company.…”
Section: Measurement Of Confoundermentioning
confidence: 99%
“…Apie kitas, rečiau pasitaikančias, būkles po procedūros informacijos kol kas yra mažiau. Viena iš jų -skausminis sindromas punkcijos vietoje po PKI, kuris gali būti sąlygotas nervo pažeidimo intervencijos metu, nervo suspaudimo tvarsčiu ar dėl susiformavusios hematomos po kraujagyslės pažeidimo [7,8]. Ūmus ir lėtinis skausmas po procedūros yra retos, tačiau labai trikdančios paciento kasdienį gyvenimą bei ribojančios jo veiksnumą būklės [13].…”
Section: įVadasunclassified
“…Femoral vessels are still used as the most common access site for the different specialties performed in hemodynamic laboratories, especially in percutaneous procedures that require the use of large-caliber introducers such as in endovascular correction of aneurysms and valvuloplasties, which further increases the potential for access site complications (5) . Among femoral approach complications, the most frequently described are bleeding, hematoma, and pseudo-aneurysm (6)(7) . The trans-radial approach is gaining popularity, especially in diagnostic and therapeutic cardiac procedures, as data regarding the safety and effectiveness of the technique emerge, associating it with lower rates of vascular complications and bleeding (8)(9) .…”
Section: Introductionmentioning
confidence: 99%
“…Although the risk of complications is low for experienced interventionists, patients must be carefully evaluated regarding signs and symptoms of bleeding and nerve compression (12) . Access site complications lead to longer periods of hospitalization, additional treatments, and higher costs, in addition to being associated with increased morbidity and mortality (6) . In the face of these repercussions, complications must be identified and monitored to prevent, minimize, or resolve potential harm to patients.…”
Section: Introductionmentioning
confidence: 99%